Oscilador H para medição de capacitâncias - Carvalho, Stéphane Santos (2025)
Capacitive sensors operate based on capacitance variation in response to a stimulus, offering a wide range of applications. Among the various measurement techniques, oscillator circuits stand out for providing a stable, direct, and reliable response. However, in applications where isolating the sensor electrodes is not feasible, the presence of a resistive component associated with capacitance—often overlooked—can compromise oscillator-based measurement systems by destabilizing the circuit and interrupting its operation, especially at high frequencies. Although the literature addresses this issue, most solutions focus solely on low-frequency applications and propose large, complex circuits, hindering the development of efficient systems and limiting the use of high-frequency sensors. In light of this, this work presents a new sinusoidal oscillator topology, based on the Colpitts oscillator, for measuring non-ideal capacitive loads in the frequency range from hundreds of kilohertz to hundreds of megahertz, referred to here as the H Oscillator. This topology is designed to maintain oscillation criteria even in the presence of variations in the sensitive elements. The scientific framework adopted for the oscillator’s development, as well as its theoretical formulation, are detailed in this work. Simulations were performed using LTSpice and QucsStudio simulation environments, employing capacitive sensor models. The results demonstrate the circuit’s robustness against parameter variations, enabling the measurement of different capacitive loads without oscillation interruption. Furthermore, the theoretical formulation was validated, with errors of only 0.78% between the expected and measured frequency variation curves and 1.47% for amplitude variation. Thus, this dissertation presents a novel approach to capacitive load sensor measurement, with potential for various applications.